2022
DOI: 10.1088/1742-6596/2309/1/012061
|View full text |Cite
|
Sign up to set email alerts
|

The importance of e-books in improving students’ skills in physics learning in the 21st century: a literature review

Abstract: Along with the development of technology, the education system began to change from face-to-face learning to blended learning. Blended learning uses a combination of print and digital learning media. Most digital learning resources are e-books that replace the function of printed books and the role of the teacher in the classroom. The focus of research in this paper is how e-books can improve student skills in the 21st century. There has been a number of researches related to e-books and their use in high scho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 20 publications
1
22
0
2
Order By: Relevance
“…Previous research concludes that there is an increase in students' critical thinking skills (Zulhelmi et al, 2017). Other studies have also shown that interactive learning media, and tutorial models, have a significant effect on students' critical thinking skills (Komara et al, 2017;Sari et al, 2022b).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research concludes that there is an increase in students' critical thinking skills (Zulhelmi et al, 2017). Other studies have also shown that interactive learning media, and tutorial models, have a significant effect on students' critical thinking skills (Komara et al, 2017;Sari et al, 2022b).…”
Section: Discussionmentioning
confidence: 99%
“…Teaching and learning activities are carried out on a limited basis by utilizing Google Meet. Teachers and students often experience a lack of time to get optimal learning outcomes (Sari et al, 2022).…”
Section: Figure 2 Concept Mapmentioning
confidence: 99%
“…The use of Android-based e-books equipped with videos and pictures attracts the attention of students and supports students in getting different experiences in the learning process (Hasbiyati, Sudiarti, & Hikamah, 2019). E-books trigger students' curiosity about physics which is very closely related to daily life (Sari, Rahim, Sundari, & Aulia, 2022). Thus, students can use smartphones positively and apply technology in education.…”
Section: Introductionmentioning
confidence: 99%
“…Salah satu yang harus diperbaiki untuk menghadapi kemajuan IPTEK adalah dalam bidang pendidikan. Hal ini dikarenakan pendidikan menjadi sarana untuk menuju pada pertumbuhan dan perkembangan bangsa (Gökçen, 2022;Sari, Rahim, Sundari, & Aulia, 2022;Suherman, Vidákovich, & Komarudin, 2021). Proses pembelajaran yang terkesan konvensional dianggap kurang optimal dalam memenuhi kebutuhan siswa serta terasa membosankan (Irwandani 2016;Darmika, Suma, & Suastra, 2014).…”
Section: Pendahuluanunclassified